Allergy diagnostic performance of FastCheckPOC 20 Atopy - Nösslinger, Hannes; Mair, Ewald; Oostingh, Gertie J.; Ahlgrimm-Siess, Verena; Ringauf, Anna; Lang, Roland (Frontiers in Allergy, 2025)
BackgroundThe increasing prevalence of allergic diseases, along with their diagnosis and treatment, presents a growing challenge in health care. To reduce this burden, a highly sensitive and specific point-of-care test for detecting sensitization could be implemented in a primary health care setting. The study aimed to investigate the accuracy of FastCheckPOC 20 Atopy (FCP20) in comparison with the multiplex assay Allergy Explorer 2 (ALEX2) system.MethodsIn this cross-sectional study, 215 participants were recruited from South Tyrol, Italy. Serum samples were analyzed using both FCP20 and ALEX2. Dichotomous data were used to calculate sensitivity and specificity in comparison with the ALEX2.ResultsThe overall sensitivity of the FCP20 was 43.3% (95% CI: 40.3%–46.2%), and the specificity was 92.1% (95% CI: 91.1%–93.0%). Inhalation allergens showed a higher sensitivity than food allergens; the grass pollen (gx17) exhibited the highest sensitivity at 79.8% (95% CI: 72.6%–85.7%). Among patients with severe allergic symptoms, bronchial asthma, or eczema, sensitivity increased to over 83%.ConclusionsFCP20 demonstrates high specificity and may be considered for the exclusion of sensitization to selected allergens, but its low sensitivity limits its utility as a general screening tool.